The Distinction between Two Sexes and its Effects in Women Empowerment and the decision making - A field stay in the province Hama (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
The p resent study aims to diagnosing the problem of gender  difference ,and the negative role it plays in the inferiority of women and not empowering  her to make decisions. The researcher used the descriptive analytical method. A questionnaire is designed to distributed among those who make the community of the study. Results were studied and analysis . The study is divided into three line: -Definition of the definition between the two sexes as perceived in the social status. -The inferiority of rural women, and the problems  she suffers from. -presenting a field study, about this ,problem biased on supposition which constitute the causes of the problem. Suggestions and recommendations  will be given that aim at finding convenient solutions. تركز الدراسة الحالية التعرف على مشكلة التمييز بين الجنسين والدور السلبي  الذي يمكن ان تلعبه في دونية المرأة و عدم تمكينها في اتخاذ القرارات في جميع المجالات,استخدم الباحث المنهج الوصفي التحليلي ,كما تم تصميم استبانة وتوزيعها على مجتمع الدراسة كما تم دراسة و تحليل البيانات باستخدام برنامج spss قسمت الدراسة الى ثلاث محاور اساسية - التعريف بالتمييز بين الجنسين من خلال الواقع الاجتماعي. - دونية المرأة في الريفو المشكلات التي تعاني منه نتيجة التمييز بين الجنسين. - تقديم دراسة ميدانية حول مشكلة التمييز و التي تعاني منها المرأةالريفية مبنية على أهم الافتراضات التي تشكل اسباب المشكلة. إضافة الى تقديم مجموعة من المقترحات و التوصيات التي تساعد في ايجاد الحلول المناسبة لها.